Telengit non-fairy folklore in studies by K. V. Yadanova - Basangova, Tamara G. (The New Research of Tuva, 2014)
Review to: Yadanova K.V. Tales, legends, true stories of Telengits. Gorno-Altaysk, 2013. 256 P.
Keywords: opinion; edition-2013; Altay; Celerity; folklore